Cardiac resynchronization therapy: association between genetically determinated dilated cardiomyopathy and dissinchronopathy. (3rd October 2022) - Bessi, R; Dal Ferro, M; Gregorio, C; Paldino, A; De Angelis, G; De Bellis, A; Mase, M; Zaffalon, D; Gigli, M; Stolfo, D; Merlo, M; Zecchin, M; et al.
Abstract: Background: Patients with non-ischemic dilated cardiomyopathy (DCM) and left bundle branch block (LBBB) often undergoes cardiac resynchronization therapy (CRT). Despite CRT only a small group of patients restore normal left ventricular geometry and function. Many predictors of response to CRT have been described, but there are still insufficient data on the role of genetic mutations in sarcomere, cytoskeletal or desmosomal genes. Purpose: To asses the role of genetic background as predictor of response after CRT in patient DCM and LBBB. Methods: We retrospectively analyzed DCM patients with successful CRT implantation and available genetic testing consecutively included in the CRT-Registry of our Institution. DCM was defined by the presence of left ventricular or biventricular dilatation and systolic dysfunction in the absence of abnormal loading conditions or coronary artery disease sufficient to cause global systolic impairment. Changes in main echocardiographic parameters: left ventricular ejection fraction (LVEF), LV End Systolic and End Diastolic Volume (LVESV and LVEDV), where compared between basal and 24–48 months of follow up. LV remodeling was defined by relative changes (Δ) in LV End Systolic Volume (LVESV) [(follow-up LVESV − PRE LVESV) / PRE LVESV × 100)]. Patients were considered super-responders (SR) if LVEF at 24–48 months was>50%. Genetic testing was done by Next Generation DNA and all variants were validated with bidirectional Sanger sequencing. Variants of uncertain significance (VUS) were excluded from the analysis. Patients being carrier of pathogenic (P) or likely pathogenic (LP) variants were considered affected by genetic DCM (GEN+ DCM). Patients non carrier of P/LP variants and with no evidence of familial disease were considered affected by non-genetically determined DCM (GEN− DCM). Results: 73 patients met the inclusion criteria, 23 patients were GEN+ DCM, the remaining 50 patients had negative genetic test and no family history of DCM. Baseline characteristics were similar between groups. GEN− group was characterized by a greater improvement in LVEF (39±12 vs 29±12, p=0, 006) and a greater relative reduction in LVESV (ΔLVESV 43% vs 18%, p=0, 007). GEN− patients had a 33 ml higher mean LVESV reduction at 24–48 months after CRT, indipendently of their respective baseline values. 20 patients (27% of the total population) suffered of heart failure related death, heart transplantation or left ventricular assistance device implantation during follow up and the prevalence was significantly higher in GEN+ group (43% vs 20%, p=0, 037). Coherently, patients in the GEN+ group showed a lower prevalence of super responders (4%, vs 24%, p=0, 02) after CRT. Conclusions: Non-genetically determined DCM DCM is associated with a better clinical and instrumental response to CRT and a higher probability of being super responders. Furthermore, our data support the hypothesis about dyssyncronopathy as a specific clinical entity inside DCM diseases. Funding Acknowledgement: Type of funding sources: None.